Does the Application of Tecar Therapy Affect Temperature and Perfusion of Skin and Muscle Microcirculation? A Pilot Feasibility Study on Healthy Subjects - Clijsen, Ron; Leoni, Diego; Schneebeli, Alessandro; Cescon, Corrado; Soldini, Emiliano; Li, Lihui; Barbero, Marco (The journal of alternative and complementary medicine (New York, N.Y.), 2020)
Background: Tecar therapy (TT) is an endogenous thermotherapy used to generate warming up of superficial and deep tissues. TT capability to affect the blood flow is commonly considered to be the primary mechanism to promote tissue healing processes. Despite some preliminary evidence about its clinical efficacy, knowledge on the physiologic responses induced by TT is lacking. Objective: The aim of this quantitative randomized pilot study was to determinate if TT, delivered in two modes (resistive and capacitive), affects the perfusion of the skin microcirculation (PSMC) and intramuscular blood flow (IMBF). Design: A randomized controlled pilot feasibility study. Subjects: Ten healthy volunteers ( n = 4 females, n = 6 males; mean age 35.9 ± 10.7 years) from a university population were recruited and completed the study. Intervention: All subjects received three different TT applications (resistive, capacitive, and placebo) for a period of 8 min. Outcome measures: PSMC, IMBF, and the skin temperature (ST) were measured pre- and post-TT application using power Doppler sonography, laser speckle contrast imaging (LSCI), and infrared thermography. Results: Compared with placebo application, statistically significant differences in PSMC resulted after both the resistive ( p = 0.0001) and the capacitive ( p = 0.0001) TT applications, while only the resistive modality compared with the placebo was capable to induce a significant change of IMBF ( p = 0.013) and ST ( p = 0.0001). Conclusions: The use of power Doppler sonography and LSCI enabled us to evaluate differences in PSMC and IMBF induced by TT application.